PENGARUH MODEL SCIENCE TECHNOLOGY SOCIETY DISERTAI TEKNIK MIND MAP TERHADAP HASIL BELAJAR BIOLOGI DAN SIKAP PEDULI LINGKUNGAN SISWA DI SMAN COLOMADU - Yanti, Ita Widya; Suciati, Suciati; Ariyanto, Joko (P Biologi FKIP UNS Surakarta, 2013)
ABSTRACT ? This research aimed to determine: (1) The effect of Science Technology Society (STS) model with Mind Map technique to Biology learning achivement grade 10th of at SMAN Colomadu Academic Year 2011/2012, (2) The effect of the application of STS model with Mind Map technique to environmental attitudes of 10th of students at SMAN Colomadu Academic Year 2011/2012. This research was Quasy Experimental Research used The Randomized Control Group Posttest Design. The population of this research were all students of SMA Colomadu Academic Year 2011/2012. The sample of this research was by cluster random sampling. The samples for this research was grade 10th.6 as the control classes with using various oral model with simple summary practice and grade 10th.2 as experimental class are using the STS learning model with the Mind Map technique. The data collection techniques is by documentation techniques, observation sheets, questionnaires, and tests. The technique of data analysis using the descriptive statistics and the inferential statistics with using t-test to test the hypothesis with the succor of SPSS 16. Based on the research can be concluded: (1) There is a significant effect of STS model with Mind Map technique on Biology learning achievement grade 10th at SMAN Colomadu Academic Year 2011/2012 with cognitive significant value 0000; psychomotor domain 0.000, and affective domain 0.019 (2) There is significant effect of STS model with Mind Map technique on environmental attitudes of class X at SMAN Colomadu Academic Year 2011/2012 with significant value 0.002. Keywords: Science Technology Society (STS) Model, Mind Map Technique, Learning Achievement, Environmental Attitudes